Skor Diskriminan Manifestasi Klinis dan Laboratorik sebagai Prediktor Syok pada Demam Berdarah Dengue - Mohamad Supriatna; MMDEAH Hapsari; Maria Mexitalia; Yusrina Istanti (MEDIA MEDIKA INDONESIANA, 2010)
Discriminant score of clinical and laboratory manifestations as a predictor of shock in dengue hemorrhagic fever Background: Case fatality rate of dengue shock syndrome (DSS) is still high. In Dr. Kariadi Hospital Semarang (RSDK) was 5.7 to 10.8% during 2000 to 2004. This is due to clinical course of dengue hemorrhagic fever (DHF) are unpredictable whether patients will develop to shock or not. We aimed to formulate discriminant score of clinical and laboratory manifestations that can be used as a predictor of shock in DHF.Methods: An observational analytic study was done. Consecutive sample were taken from DHF patients aged 3–14 years who were treated at RSDK in February 2001–March 2003. Diagnosis was established based on WHO 1997 criteria and serologic indirect-ELISA. Septic children were excluded. Clinical and laboratory manifestations were examined at admission or when diagnosed as DHF. Chi-square, Mann-Whitney, and discriminant analysis were done to formulate discriminant score.Results: There were 152 DHF patients enrolled, consist of 61 non-DSS and 91 DSS. Discriminant score formulation was obtained as: D=–1.103 + (0.013 x bleeding type) + (1.229 x vomiting) + (0.478 x abdominal pain) + (0.922 x hepatomegaly) – (0.039 x haemoglobin) + (0.014 x haematocryt) – (0.404 x albumin) – (0.046 x total protein) + (0.043 x pleural effusion index). Discriminant score mean for DSS is +0.739 and non-DSS –1.103 with cut-off point of –0.182. If the score <–0.182 patients become non-SSD and ≥–0.182 DSS. Conclusion: Discriminant score of clinical and laboratory manifestations can be used as a predictor of shock in DHF with prediction accuracy of 80.3%.ABSTRAKLatar belakang: Angka kematian sindrom syok dengue (SSD) masih tinggi. Di RSUP Dr. Kariadi (RSDK) Semarang 5,7–10,8% pada tahun 2000–2004. Hal ini disebabkan perjalanan klinis demam berdarah dengue (DBD) sulit diprediksi apakah penderita akan mengalami syok atau tidak. Tujuan penelitian adalah merumuskan skor diskriminan manifestasi klinis dan laboratoris yang dapat dijadikan sebagai prediktor syok pada DBD. Metoda: Dilakukan penelitian observasional analitik dengan sampel secara consecutive dari penderita DBD umur 3–14 tahun yang dirawat di RSDK pada Februari 2001–Maret 2003. Diagnosis ditegakkan berdasar kriteria WHO 1997 dan serologis indirect-ELISA. Anak dengan sepsis dieksklusi dari penelitian. Manifestasi klinis dan laboratoris diperiksa saat masuk rumah sakit atau saat diagnosis ditegakkan. Uji Chi-square, Mann-Whitney, dan analisis diskriminan dilakukan untuk merumuskan skor diskriminan.Hasil: Didapatkan 152 penderita DBD yang terdiri dari 61 non-SSD dan 91 SSD. Rumus skor diskriminan yang didapat sebagai berikut: D=–1,103 + (0,013 x jenis perdarahan) + (1,229 x muntah) + (0,478 x nyeri perut) + (0,922 x hepatomegali) – (0,039 x hemoglobin) + (0,014 x hematokrit) – (0,404 x albumin) – (0,046 x protein total) + (0,043 x indeks efusi pleura).Rerata skor diskriminan SSD +0,739 dan non-SSD –1,103 dengan cut off point –0,182. Bila skor <–0,182 penderita akan menjadi non-SSD dan ≥–0,182 akan menjadi SSD. Simpulan: Skor diskriminan manifestasi klinis dan laboratoris dapat dijadikan sebagai prediktor syok pada DBD dengan 80,3% ketepatan prediksi.